Pengaruh Penyuluhan Bahaya Seks Bebas pada Remaja Di Madrasah Aliyah Negeri (MAN) 3 Indrapuri Aceh Besar - Suryani, Linda; Fuadi, Tuti Marjan; Keumala, Cut Ratna; Mardelita, Sisca; Andriani; Liana, Intan (Poltekkes Kemenkes Aceh, 2023)
Aceh as a province with the implementation of Islamic law is not necessarily free from the problem of teenage promiscuity. Free sex among adolescents in Aceh can be seen from the various cases of adolescents who become pregnant at school age, the spread of sexually transmitted diseases is also increasing, abortions and early marriages are increasingly common. Socounseling related to free sex among adolescents is very necessary. The purpose of this study was to determine the effect of counseling on the dangers of free sex on adolescents at Madrasah Aliyah Negeri (MAN) 3 Indrapuri Aceh Besar. The design of this study was to use a quasi-experimental design with a one group pretest and posttest approach, where the selection of the intervention group was then carried out pre (before) and post (after). The sampling technique used saturated sampling with a sample size of 37 students. The results of the Wilcoxon sigh rank test with a confidence level of 95% (α = 0.005) obtained a p value of 0.000 <0.005. So it can be concluded that there is an influence of counseling on the dangers of free sex on adolescent knowledge about free sex at Madrasah Aliyah Negeri (MAN) 3 Indrapuri Aceh Besar.